Anti Vaccination: Human Right or Public Interest - Winda Wijayanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Covid-19 virus has caused numerous deaths across the country. Vaccination as an effort to break the chain of spreading the virus is hampered due to misinformation. Public ignorance of the importance of vaccines to inhibit and destroy viruses is very detrimental to public health rights. As good citizens, they should obey government policies. In reality, some movements harm movements that harm public health rights. The community movement as a form of public participation to provide input to the government on government policies should be to fight for the interests of the community based on accurate and useful information in Indonesian territory. This article is legal research related to the protection of citizens for public health rights as a fulfillment of human rights. The articles have two problems. First, whether the refusal of vaccination violates the law, and second, how the state protects the right to public health. The refusal to vaccinate is against the protection in the 1945 Constitution of the Republic of Indonesia. In the future, there is a need for public participation in the rule of law as an effort to defend the state in formulating appropriate sanctions and the social media to the public interest.